Stakeholders in the law school - Cownie, Fiona (Hart, 2010)
"This collection brings together a distinguished group of researchers to examine the power relations which are played out in university law schools as a result of the different pressures exerted upon them by a range of different 'stakeholders'. From students to governments, from lawyers to universities, a host of institutions and actors believe that law schools should take account of a vast number of (often conflicting) considerations when teaching their students, designing curricula, carrying out research and so on. How do law schools deal with these pressures? What should their response be to the 'stakeholders' who urge them to follow agendas emanating from outside the law school itself? To what extent should some of these agendas play a greater role in the thinking of law schools? These issues resonate throughout this collection."--Jacket